Pengaruh Cara Berfikir Logis Terhadap Kemampuan Menyelesaikan Soal Logika Pada Siswa Kelas 11 - Islamy, Diah Putri; Indrawati, Indrawati (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
The ability to think logically has a very important role in the learning process, because high logical thinking abilities can guide students to solve problems accurately and purposefully. Logic material is a type of mathematical material that prioritizes logical thinking in every problem solution. Students often experience confusion when solving logic problems, even though logic material is material that does not use number calculations, students often do not understand logic problems which results in low learning grades. This research was conducted on 50 grade 11 students at Mandiri Palembang High School. The aim of this research is to see how much influence students' logical thinking abilities have in solving mathematical logic problems. Statistical testing in this study used simple regression analysis by conducting a t test using the SPSS 26.00 application. Data collection in this study used tests in the form of questions to measure students' thinking abilities in solving logical problems. The research results show that the t value > t tabel is 2.963 which is greater than the t tabel of 1.993. This shows that there is an influence on grade 11 students' logical thinking abilities on their ability to solve logical problems.